Effects of Mental Health Support on the Grief of Bereaved People Caused by Sewol Ferry Accident - Han, Hyesung; Noh, Jin-Won; Huh, Hyu jung; Huh, Seung; Joo, Ji-Young; Hong, Jin Hyuk; Chae, Jeong-Ho (Journal of Korean medical science, 2017)
Few studies have assessed the overall effects of multi-centered, complicated mental health support on the grief process. This study investigated the broader influence of mental health support provided practically to the bereaved family on the severity of complicated grief. Ninety-three bereaved family members of the Sewol ferry accident were recruited. Severity of complicated grief, post-traumatic stress disorder (PTSD) and depressive disorder was assessed through self-reporting questionnaire, inventory of complicated grief (ICG), PTSD Check List-5 (PCL-5) and Patient Health Questionnaire-9 (PHQ-9). We also included demographic, socioeconomic, health-related variables, and Functional Social Support Questionnaire (FSSQ), which affect the ICG score. Participants were divided into 4 groups based on the experience of psychotherapy or psychiatry clinic service before the accident and mental health support after the disaster. In univariate analysis, these 4 groups showed a significant difference in the mean ICG score (P = 0.020). Participants who received mental health support only after the Sewol ferry accident (group 2) showed a lower mean ICG score than those who received neither psychotherapy or psychiatry clinic service before the disaster nor mental health support after the accident (group 4). There was no significant correlation between the ICG score and other variables except for subjective health status measured 1 month after the disaster (P = 0.005). There was no significant difference in PCL-5 (P = 0.140) and PHQ-9 scores (P = 0.603) among groups, respectively. In conclusion, mental health support significantly reduced the severity of grief only in those participants who had not received any psychotherapy or psychiatry clinic service before the accident.